Chimpanzee brain morphometry utilizing standardized MRI preprocessing and macroanatomical annotations - Vickery, Sam; Hopkins, William D; Sherwood, Chet C; Schapiro, Steven J; Latzman, Robert D; Caspers, Svenja; Gaser, Christian; Eickhoff, Simon B; Dahnke, Robert; Hoffstaedter, Felix (eLife, 2020)
Chimpanzees are among the closest living relatives to humans and, as such, provide a crucial comparative model for investigating primate brain evolution. In recent years, human brain mapping has strongly benefited from enhanced computational models and image processing pipelines that could also improve data analyses in animals by using species-specific templates. In this study, we use structural MRI data from the National Chimpanzee Brain Resource (NCBR) to develop the chimpanzee brain reference template Juna.Chimp for spatial registration and the macro-anatomical brain parcellation Davi130 for standardized whole-brain analysis. Additionally, we introduce a ready-to-use image processing pipeline built upon the CAT12 toolbox in SPM12, implementing a standard human image preprocessing framework in chimpanzees. Applying this approach to data from 194 subjects, we find strong evidence for human-like age-related gray matter atrophy in multiple regions of the chimpanzee brain, as well as, a general rightward asymmetry in brain regions.